2004
DOI: 10.1002/cyto.b.20021
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex bead array assays for detection of soluble cytokines: Comparisons of sensitivity and quantitative values among kits from multiple manufacturers

Abstract: Background: Multiplex bead array assays permit simultaneous cytometric quantitation of multiple cytokines in solution by capturing these to spectrally distinct beads. Because several manufacturers offer reagents to quantitate the same cytokines on a single instrument, a comparison should be made to determine whether these kits yield similar data and whether these data are comparable to enzyme-linked immunosorbent assay (ELISA).Methods: This study compared cytokine detection kits by using Luminex 100. Twenty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
179
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(189 citation statements)
references
References 18 publications
7
179
0
1
Order By: Relevance
“…Indeed, we confirmed that the absolute values of the proteins detected were different between the two tested technologies. Such discordance could be due to differences in the capture and/or detection antibodies and to a differential sensitivity to matrix interference (Dupuy et al, 2013;Khan et al, 2004). However, among the cytokines for which the quantification was consistent, we observed strong inter-platform correlations for IL-8 and VEGF (Table 5), in accordance with previous findings (Chowdhury et al, 2009;Dabitao et al, 2011;Huttunen et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, we confirmed that the absolute values of the proteins detected were different between the two tested technologies. Such discordance could be due to differences in the capture and/or detection antibodies and to a differential sensitivity to matrix interference (Dupuy et al, 2013;Khan et al, 2004). However, among the cytokines for which the quantification was consistent, we observed strong inter-platform correlations for IL-8 and VEGF (Table 5), in accordance with previous findings (Chowdhury et al, 2009;Dabitao et al, 2011;Huttunen et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…It has already been stressed out that the comparison of absolute cytokine concentration should be attempted only if used reagents were obtained from the same supplier (Khan et al, 2004), although even singleplex assays compared to multiplex assays from the same company can yield significantly different results (de Koning et al, 2012;Huttunen et al, 2014). Indeed, we confirmed that the absolute values of the proteins detected were different between the two tested technologies.…”
Section: Discussionsupporting
confidence: 61%
“…With this in mind, any study that involves sequential monitoring of patients, or other samples, should be performed using only a single technique, one platform, and one commercial vendor for all samples. As illustrated by Khan et al, although multiplex assays from different vendors will show similar trends in cytokine levels, the absolute levels of cytokines measured will vary (22). Therefore, even MBAA assays from different vendors should not be considered interchangeable.…”
Section: Discussionmentioning
confidence: 99%
“…Although commercially available kits have been extensively characterized and qualified by their respective manufacturers, there are a limited number of peer-reviewed reports of direct comparisons between multiplex bead arrays and ELISA kits, and all of these have been published within the last decade (3,5,(21)(22)(23)(24)(25)(26)(27)(28). It is difficult to compare the data from the different studies, as various investigators used different methods of comparison between MBAA and ELISAs, and reports varied considerably in the amount of methodological detail provided.…”
Section: Comparison Of Multiplex Bead Arrays Vs Elisasmentioning
confidence: 99%
“…Culture supernatants were harvested after 72 hours and stored at Ϫ80°C until further analyzed. Extracellular cytokines and chemokines were measured using a multiplex immunoassay (Luminex, Austin, TX) as previously described (36)(37)(38). In summary, the antibodycoated microspheres were incubated for 60 minutes with standards or culture medium (25 l) in 96-well, 1.2-m filter plates (Millipore, Amsterdam, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%